Maritime traffic alters distribution of the harbour porpoise in the North Sea - Pigeault, Rémi; Ruser, Andreas; Ramírez-Martínez, Nadya C.; Geelhoed, Steve C.V.; Haelters, Jan; Nachtsheim, Dominik A.; Schaffeld, Tobias; Sveegaard, Signe; Siebert, Ursula; Gilles, Anita (Marine Pollution Bulletin, 2024)
The North Sea is one of the most industrialised marine regions globally. We integrated cetacean-dedicated aerial surveys (2015–2022) with environmental covariates and ship positions from the Automatic Identification System (AIS) to investigate the disturbance radius and duration on harbour porpoise distribution. This study is based on 81,511 km of line-transect survey effort, during which 6511 harbour porpoise groups (8597 individuals) were sighted. Several proxies for ship disturbance were compared, identifying those best explaining the observed distribution. Better model performance was achieved by integrating maritime traffic, with frequent traffic representing the most significant disturbance to harbour porpoise distribution. Porpoises avoided areas frequented by numerous vessels up to distances of 9 km. The number of ships and average approach distance over time improved model performance, while reasons for the lower performance of predicted ship sound levels remain unclear. This study demonstrates the short-term effects of maritime traffic on harbour porpoise distribution.